Strangers at Home: The Unheimliche in Yehudit Hendel’s Oeuvre - Milner, Iris (MiKAN, 2016)
Yehudit Hendel (1921-2014) is one of the most provocative Modern Hebrew writers; her oeuvre consistently exposes covert layers underneath hegemonic Israeli narratives and pays empathic attention to marginal, oppositional voices that question these narratives’ validity. The present essay explores how this takes place in relation to the concept and ideology of the Israeli home. It discusses Hendel’s subversive representation of the home and the literary strategies by which her works question and often reject the myth of the home, both on a social national level (the national home as a refuge from threats to Jewish existence) and on a private level. Accordingly, the essay reads the representation of the home both in Hendel’s early novels and in her more recent short stories as a site of the Unheimliche – the Unhomely, in Freudian terms. It shows that the image of the home – a highly prevalent one in Hendel’s works – is often meticulously portrayed as highly unstable and fragile and thus extremely threatening. By demonstrating the dynamics of these unhomely characteristics and their sources (longings for forlorn homes elsewhere, haunting ghosts of previous Palestinian inhabitants, a desire for exilic being, etc.), the essay presents the works under discussion as a manifesto of alienation and estrangement that deconstructs the common Hebrew literary narrative of a redemptive return to a mythological homeland.